Spatial Visualization in Construction Management Education: A Review and Validation of the Literature Using Professionals and Related Practitioners. Issue 1 (2nd January 2022) - Porter, Dale; Glick, Scott
ABSTRACT: Little research exists concerning the differences of spatial abilities among Construction Professionals (CP) compared to other STEM and Non-STEM Professionals. The literature on spatial abilities in STEM vocations was reviewed and summarized to form research questions to test practitioners' perceptions on spatial abilities. This study used a survey and the Purdue Spatial Visualization Test: Rotations (PSVT:R) to identify if specific activities, experiences, or education are perceived to improve mental rotation abilities among practicing construction/related fields professionals. Differences in spatial ability were measured and a statistically significant difference was found between CPs and Non-STEM Professionals ( p =.016). Results suggest that the activity of drawing to enhancing spatial ability was attributed more frequently among high scoring individuals (52%) than low scoring individuals (15%). PSVT:R scores were also compared with the amount of time per day participants made use of their spatial abilities and no statistically significant difference was found. Findings from this study suggest that a high level of spatial abilities are present among Construction Professionals. Construction education curriculum benefits from the findings that suggest drawing is an important activity to increase one's spatial ability and should remain in CM program curriculum.